Implementation of Project-Based Learning and Critical Thinking on Students’ Learning Outcomes - Yuda Ganda Putra; Yayat Ruhiat; Lukman Nulhakim; Endang Iryani (Jurnal Penelitian Pendidikan IPA, 2025)
This study seeks to assess the impact of critical thinking and project-based learning on student learning outcomes. This study employs a mixed-methods approach that integrates qualitative and quantitative research. This study employs an Explanatory Sequential Design and encompasses a cohort of 200 students. The random sampling method is employed for the sampling procedure. The researcher performed interviews with informants to acquire further information following the conclusion of data collection. The subsequent phase entails the administration of assessments to evaluate science learning results, after the collection of quantitative data using observation sheets, questionnaires, and test items. The preliminary approach of quantitative data analysis employs SPSS Statistics 26 software to produce descriptive statistics, assess hypotheses, and examine assumptions. Furthermore, for qualitative analysis employing the Miles and Huberman methodology. The hypothesis test results indicated that PBL significantly influenced student learning outcomes (Sig. = 0.005, correlation coefficient = 0.879), critical thinking also significantly affected student learning outcomes (Sig. = 0.002, correlation coefficient = 0.880), and both project-based learning and critical thinking collectively impacted student learning outcomes (Sig. = 0.000, correlation coefficient = 0.950). Implications for educational practices and curriculum development are derived from the results of this research. Initially, the investigation endorses the integration of critical thinking and project-based learning (PBL) exercises as a means to enhance knowledge retention, and ability to apply concepts in real-world contexts.